Macroeconomic Determinants of Food Security in Ghana - Alnaa, Samuel Erasmus; Matey, Jaubin (NCC Journal, 2025)
Hunger remains a persistent development challenge in sub-Saharan Africa, and Ghana is no exception, despite decades of policy interventions and economic growth. This study examines the macroeconomic factors influencing food security in Ghana from 2001 to 2022, focusing on public agricultural employment, agricultural expenditure, and food inflation. Using ordinary least squares regression with robust standard errors, the analysis accounts for potential heteroskedasticity and autocorrelation. The results show that greater government spending on agriculture significantly lowers hunger rates, emphasizing the importance of targeted rural investment. Conversely, a higher share of agricultural employment is linked with greater hunger, reflecting the low productivity of subsistence farming and the need for structural transformation. Rising food inflation worsens food insecurity by eroding household purchasing power. The findings support the Structural Transformation Theory and recent evidence. The study recommends expanding rural investments, modernizing the agricultural sector, and strengthening food price stabilization to advance progress toward Zero Hunger in Ghana.